IMPLEMENTASI PENATAAN RUANG KAWASAN PERKOTAAN UNTUK RESAPAN AIR DI KELURAHAN KANAAN DAN GUNUNG TELIHAN KOTA BONTANG - Andi Tenri Rawe; Aji Ratna Kusuma; Fajar Apriani (Program Studi Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
Spatial planning in the city of Bontang is regulated in Regional Regulation Number 11 of 2012 concerning the Spatial Plan of the Bontang City from 2012 to 2032. This study is intended to analyze the implementation of urban spatial planning for water catchment areas based on the regional regulations and to explain the factors that support and hinder it. This study uses a qualitatitve descriptive method with a research focus on the implementation of urban spatial planning for water catchment areas which includes (1) spatial planning integration, (2) spatial harmony and balance, (3) spatial planning sustainability, (4) spatial planning success, (5) the legal certainty of spatial planning and the factors that influence the implementation of the policy are based on the Edwards III model. Tha findings in this study indicate that the implementation of Bontang City Regional Regulation Spatial Planning from 2012 to 2032 in Bontang City in urban area spatial planning for water catchment areas in Kanaan and Mount Telihan Villages has been implemented, but has not been running optimally because there are still people who violate spatial planning and preventive actions have not been optimized. The inhibiting factor is the lack of communication in the form of socialization to the community so that understanding of regional regualations is still not evenly distributed in the community.